1998
DOI: 10.1046/j.1365-2842.1998.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical mechanisms involved in the genesis of temporomandibular joint sounds

Abstract: Several different mechanisms are potentially capable of generating sounds in the temporomandibular joint (TMJ). These include impact, sliding and stick-slip friction, fluid dynamic effects and the release of elastic strain energy. It is the aim of this paper to provide a framework with which to separate sounds resulting from the different underlying causes. Each mechanism is described and its relevance to TMJ sounds and clinical significance discussed. Since it is not possible to observe these mechanisms in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
4
0
3
Order By: Relevance
“…Clicking is usually regarded as a DDR sound 6,11 , but it can be found in DDNR and even sometimes in the degenerated disease 13 . In this study, a characteristic waveform was found for sounds from all the DDR joints, but it had no relation with audible clicking in time; it is not the waveform of clicking.…”
Section: Discussionmentioning
confidence: 99%
“…Clicking is usually regarded as a DDR sound 6,11 , but it can be found in DDNR and even sometimes in the degenerated disease 13 . In this study, a characteristic waveform was found for sounds from all the DDR joints, but it had no relation with audible clicking in time; it is not the waveform of clicking.…”
Section: Discussionmentioning
confidence: 99%
“…Joint sounds are generally associated with intracapsular events (PRINZ, 1998). The possible causes of sounds are structural alterations, and the most frequent are hypermobility of the condyle-disk complex, displacement of the articular disc to the anterior, structural alterations of the articular surface, in addition to degenerative processes, which cause crackles (PRINZ, 1998). ;CONTI et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, sounds may be heard in individuals who may or may not present the typical symptoms of temporomandibular disorders (TMD) (1). Different mechanisms are involved in the occurrence of TMJ sounds, which probably reflect some abnormality in the structure and function of the joint, such as the impact between joint structures, the deformation of these structures, and the changes in the quality of the synovial fluid.…”
Section: Introductionmentioning
confidence: 99%